Die Kirche in der Krise in der Krise: Sozialethische Überlegungen zu einer politischen Diakonie der Kirche im Kontext einer doppelten Krise - Kruip, Gerhard (ET studies, 2010)
The first chapter of the following paper describes the very different kinds of interpreting the financial crisis of the years 2008-2009 in the German public discussions. For some, it is a crisis of free market in general, or even of western culture and rationality. There is a lot of artificial dramatizing in this discussion, so as if before the crisis no one had seen the dangers of an instability of the international financial system, so as if before all had opted for a laissez-faire free market economic system, so as if no regulation at all had been applied before. The author shows, that such a manner of analysing the crisis won’t help at all to resolve it. In the second chapter, some reports on the crisis by important international organizations such as Worldbank or European Central Bank are presented. Only by such a very detailed search for the causes of the crisis, the means for necessary reforms towards a better international financial architecture can be found. The third chapter deals with the contribution of Catholic Church to the solution of the crisis. From the background of the above mentioned deeper analysis, declarations of the Catholic Church about the crisis, above all the first social encyclical of Pope Benedict XVI , don’t seem to be very helpful. The encyclical emphasizes individual perspectives and does not give orientations for the necessary institutional and structural changes. The Pope finds it necessary to found moral norms in Christian truth only and therefore is not able to rely on interreligious and intercultural dialogue to find a common ground for orientation in modern pluralistic societies. But the Church finds itself in a deep crisis (chapter four), due to recent sexual abuse scandals and the way, how the Church handled it. The Church lost great part of its public credibility. It seems, that the Church above all wants to conserve its own interests as a religious institution and acts corresponding to a kind of "reasons of Church", and is less interested in the solution of the real problems humankind has today. But trying to defend the Church by isolating it in a kind of corral or laager against its supposed enemies won’t enable it for the future.